Correlation of intra-abdominal pressure with the outcome of perforation peritonitis - Agrawal, Saurabh; Chaudhary, Tarun; Sahu, Shantanu Kumar (International Surgery Journal, 2017)
Background: A progressive increase in intra-abdominal pressure (IAP) may cause abdominal compartment syndrome (ACS) with organ dysfunction. Studies have documented the impact of Intra-abdominal hypertension (IAH) on virtually every organ. However, it remains strangely underdiagnosed. Present study was aimed to correlate Intra- abdominal pressure with the outcome in perforation peritonitis patients. Methods: This study was done on 50 patients with perforation peritonitis and patients undergoing intervention in the form of either emergency laparotomy or drain placement. The abdominal pressures were indirectly determined by measuring urinary bladder pressure with a Foley's catheter. Pearson correlation was used to see relation between intra-abdominal pressure and outcome of peritonitis. Results: Mean intra-abdominal pressure during time of presentation to the hospital was 26.7±3.2cm H2O. Among various morbidities following operation, surgical site infection was most common (38%) followed by wound dehiscence (24%). There was weak linear correlation between intra-abdominal pressure and factors determining morbidity such as surgical site infection, wound dehiscence, burst abdomen, prolonged ileus, ARDS and ARF. However, this was not statistically significant. Conclusions: There is weak correlation of various co morbidities with increased intra-abdominal pressure in patients with perforation peritonitis which was not significant statistically.